Myocardial Perfusion and Coronary Physiology Assessment of Microvascular Dysfunction in Patients Undergoing Transcatheter Aortic Valve Implantation—Rationale and Design - M. M. Dobrolinska; P. Gąsior; A. Błach; R. Gocoł; D. Hudziak; W. Wojakowski (Biomimetics, 2022)
The prevalence of coronary artery disease (CAD) in patients with severe aortic stenosis (AS) is 30–68%. Nevertheless, there is still not enough evidence to use invasive assessment of lesion severity, because the hemodynamic milieu of AS may impact the fractional flow reserve (FFR) and non-hyperemic indices. Therefore, the aim of the study is two-fold. First, to measure acute and long-term changes of FFR, index of microvascular resistance (IMR), and coronary flow reserve (CFR) in patients undergoing TAVI procedure. Second, to compare the diagnostic accuracy of intracoronary indices with myocardial perfusion measured by cadmium-zinc-telluride single-photon emission tomography (CZT-SPECT) and find cut-off values defining significant stenosis. We plan to enroll 40 patients eligible for TAVI with intermediate stenosis (30–70%) in the left anterior descending (LAD) coronary artery. In each patient FFR, CFR, and IMR will be measured in addition to myocardial blood flow calculated by CZT-SPECT before and either immediately after TAVI (acute cohort) or in 6 months (late cohort) after the procedure. FFR, CFR, and IMR will be matched with the results of myocardial perfusion measured by CZT-SPECT in the area of LAD. As a result, cut-off values of FFR, CFR, and IMR defining the decreased blood flow will be found.